The common law of intellectual property : essays in honour of Professor David Vaver - Ng, Catherine Wai-Man; Bently, Lionel, 1964-; D'Agostino, Giuseppina, 1973-; Vaver, D. (Hart Pub., 2010)
This collection of essays was written in honour of David Vaver, who recently retired as Professor of Intellectual Property and Information Technology Law and Director of the Oxford Intellectual Property Research Centre at the University of Oxford. The essays, written by some of the world's leading academics, practitioners and judges in the field of intellectual property law, take as their starting point the common assumption that the patent, copyright and trade mark laws within members of the 'common law family' (Australia, Canada, Israel, Singapore, South Africa, the United Kingdom, the Unite